Dividend and excess return in China - Da, Jiaqi; Md Nassir, Annuar; Tek, Andrew Wei Saw; Zhang, Hui; Lau, Wei Theng (Penerbit Universiti Sains Malaysia, 2023)
Investors are always chasing excess returns. To examine the three driving factors affecting China A-share excess returns, namely systematic risk, idiosyncratic risk and market sentiment, this study divided A-shares into non-dividend and dividend-paying groups based on the Dividend Paid for Common Shares in the notes of the financial report. In addition, this study used the Capital Asset Pricing model, Single-Index model, Arbitrage Pricing theory and Fama“French three- and five-factor model to analyse the three main driving factors. The Gibbons-Ross-Shanken test was used to test the model validity, and the optimal model for each group was extracted. Our findings show that after analysing the optimal models within each group, it becomes evident that systematic risk indeed exerts an influence on both dividend-paying and non-dividend companies. Nevertheless, when considering four specific systematic risks (inflation, exchange rates, crude oil and interest rates), this studys findings establish that these risks do not significantly impact the stock returns of any company group across all time periods. As for idiosyncratic risks, firm size and book-to-market factors emerge as substantial influencers across all firms. Additionally, market sentiment significantly affects the stock performance of small-sized dividend-paying companies.